Optimal Distributed Control for the Processes of Oscillation Described by Fredholm Integro-Differential Equations - Kerimbekov, Akylbek K.; Abdyldaeva, Elmira F. (Eurasian Mathematical Journal, 2015)
In this paper we investigate the problem of distributed optimal control for the oscillation processes described by Fredholm integro-differential equations with partial derivatives when the function of the external source depends nonlinearly on the control parameters. We have developed an algorithm for finding approximate solutions of nonlinear optimization problems with arbitrary precision. The developed method of solving nonlinear optimization problems is constructive and can be used in applications.